Synthesis of Silver Nanoparticles Using Ionic-Liquid-Based Microwave-Assisted Extraction from Polygonum minus and Photodegradation of Methylene Blue - Ullah, H. (Chinese Chemical Society Taiwan, 2017)
A green biogenic, nontoxic, high-yielding synthetic method is introduced for the synthesis of silver nanoparticles (AgNPs) using ionic-liquid-based, microwave-assisted extraction (ILMAE) from Polygonum minus. The aqueous ionic liquid (1-butyl-3-methylimidazolium chloride BMIMCl)-based plant extract was used as reducing agent to reduce silver ions to AgNPs. The synthesis of AgNPs was confirmed by UV–visible spectrophotometry. Fourier transforms infrared (FTIR) spectra showed that the plant bioactive compounds capped the AgNPs. The particle size and morphology of Ag NPs were characterized by dynamic light scattering (DLS) and field emission scanning electron microscopy (FESEM), respectively. Elemental analysis was carried out by energy-dispersive X-ray (EDX) spectroscopy. Photodegradation studies showed that the AgNPs degraded 98% of methylene blue in 12 min. © 2017 The Chemical Society Located in Taipei & Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim